Korban Penyalahgunaan Narkotika dibawah 1 gram harus direhabilitasi Bukan Pidana Penjara - Bandaharo Saifuddin (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2019)
This paper discusses the issue to be achieved for victims of narcotics abuse below 1 gram must be rehabilitated, not imprisoned, because Narcotics users as victims who accidentally use narcotics because they are cheated, tricked, forced and or threatened, so they need rehabilitation. Victims of Narcotics users below 1 gram are always faced with a trial for violating Article 127 paragraph 1 letter a of Law Number 35 Year 2009 and adjudicated by the judge with a prison sentence instead of being rehabilitated. The method used by the author is a normative and empirical research method with suber information from primary and secondary materials. The data collection method uses document studies by analyzing data and using hypothesis testing techniques based on induction and deduction. The result was that almost all victims of narcotics use in court were sentenced by judges to imprisonment. The conclusion that the imprisonment of the defendant is the ultimum remendium which if the level is below 1 gram should be rehabilitated instead of imprisonment.Key words: Victims of Narcotics Abuse; Criminal Prison; Rehabilitation